Assessing of land use land cover impact on flood in Kemaman River Basin - Nurulashikin, Khalil @ Azmi (2017)
Land use land cover (LULC) changes affected the hydrological cycle and water yield availability. Water yield increase up to 190% after forest clearing for agricultural activity in Peninsular Malaysia. Access water-yield could be able flooding any area. The study main objective were assessing of LULC impact on flood in Kemaman River Basin. To achieve the study main objective, the specific study were performed as follows, to analyse the rainfall, actual evapotranspiration (AET) and water surplus (water-yield), and the LULC impact on flood in Kemaman River Basin. In December 2014 flood was greater than the flood in December 2013. This is due to the high intensity of rainfall 1477.8 mm and 94% (1385.9 mm) from the product water. In addition, a reduction in stand LULC vegetative (11.07% in 2013 to 9.11% in 2014) due to crop and replanting activities is shown by the reduction of AET (99.55 mm in 2013 and 91.96 mm in 2014). From these findings, it is recommended replanting scheme is taken into account in the design of non-structure flood mitigation.